Manuel de gestion du mobilier archéologique Méthodologie et pratiques - Païn, Silvia (Documents d'archéologie française, 2015)
The management of archaeological artefacts calls upon knowledge and practices originating in diverse disciplines, which Silvia Païn, a respected conservation-restoration specialist, presents here to professionals. The different situations faced while performing this work are addressed in methodological terms and in these pages professionals will find the tools necessary to develop their procedure and management system in a global manner. They will also find all of the practical advice necessary to ensure the long term conservation of remains and to guarantee their accessibility to researchers. A thorough knowledge of the material and its alteration is the foundation of the conservation procedure: Païn argues that it is essential to take into account the transformations undergone by the material while it is buried and when it is uncovered since the definition of indispensable preventive measures must be based on an informed evaluation of the risks. In effect, throughout the course of an object's existence -from its discovery to its study- its conservation consists of interventions that are integrated within a coherent and continual process. Managing the material also implies ensuring its physical and intellectual accessibility: the reader will find useful advice on how to create an inventory and preserve the associated records, broadly understood as the link between the object, its data, the documentation generated by it and its field records. The reader will learn to how to develop material and computer-based infrastructures based on a detailed consideration of the activities of their users, while integrating the issues surrounding the optimal use of storage spaces. At the end of this work, Païn reviews the regulatory and legal obligations of rescue archaeologists, depositary personnel, owners and legal representatives. The current regulations are also presented, along with recommendations for developing or modifying those of the structure in which the artefact manager is working. In this complete and up-to-date manual, the conservation-restoration professional, artefact manager, and more broadly, archaeologists and their administrators, will find an indispensable tool for their daily practices.